Estudio comparativo de la influencia de las actitudes erotofílicas - erotofóbicas en la culpabilidad sexual en adolescentes de 15 a 19 años de edad de las Instituciones Educativas Eduardo Mora Moreno de la zona rural y Benardo Valdivieso de la zona urbana de la ciudad de Loja, periodo 2019 - Pucha Loarte, Tatiana Isabel (2019)
Addressing sexuality on the basis of myths, taboos and prejudices predisposes to the formation of erotophobic sexual attitudes, which predisposes the development of psychological alterations, such as sexual guilt that without proper might generate anxiety and depression. Regardless, there are few studies and knowledge about these variables in one of the most vulnerable stages of life, such as adolescence. Therefore, this research work aims to compare the influence exerted by attitudes erotophobic sex-erotophilic in sexual guilt in adolescents from two educational institutions from the urban and rural areas. In order to pursue this end, information was collected from 140 male and female adolescents, 70 from the "Bernardo Valdivieso" school and 70 from the "Eduardo Mora Moreno" school. The research is descriptive, transversal and comparative, with a quantitative approach; for the collection of data the sociodemographic questionnaire designed by the researcher was used, the Adapted Sexual Opinion Scale and Mosher’s Revised Sexual Guilt Inventory. The information obtained from the instruments shows that there is a predominance of moderate attitudes towards sexuality in the urban area (62, 9%) and erotophobic attitudes in the rural area (51, 4%). Moderate sexual guilt prevails in both urban (98, 6 %) and rural areas (90%). No statistically significant relationship was found between sociodemographic factors and sexual guilt in any area and erotophobic attitudes were finally found-erotophilic do not influence the presence of sexual guilt in any of the populations. Keywords: sexual attitudes, sexual guilt, adolescents, erotophobic, erotophilic